ChemInform Abstract: Direct Conversion of Haloarenes to Phenols under Mild, Transition‐Metal‐Free Conditions. Issue 37 (August 2016) - Fier, Patrick S.; Maloney, Kevin M.
Abstract: by a novel SN Ar reaction/Lossen rearrangement sequence using acetohydroxamic acid as hydroxide source